Safety and efficacy of a Salmonella Gallinarum ΔcobSΔcbiA strain with potential to prevent chicken infections by Salmonella Gallinarum and Salmonella Enteritidis - Paiva, J. B. [UNESP]; Penha Filho, R. A C [UNESP]; Moura, B. S. [UNESP]; Berchieri, A. [UNESP] (FapUNIFESP (SciELO), 2012)
New vaccine design techniques have allowed the development of effective vaccine strains against Salmonella infections in which the risks of reversion to the wild type and virulence is null. The mutant strain Salmonella Gallinarum ΔcobSΔcbiA was previously shown to be avirulent in chickens. In this study, this strain was tested as a vaccine against Salmonella Gallinarum (SG) and S. Enteritidis (SE) infections, and its protection levels, safety and possible risks of reversion to virulence after vaccination of layers were evaluated. Birds were vaccinated at five days of age or at five and 25 days of age. At 45 days of age, brown and white layers were challenged with SG and SE wild strains, respectively. Two assays to test the possibility of reversion to virulence were performed. Five successive bacterial passages in brown layers were carried out in the first assay. In the second assay, brown layers received a ten-fold concentrated inoculum of the SGΔcobSΔcbiA strain and were evaluated for clinical signs and mortality. In both experiments, no birds that received the inoculation of the attenuated strain died. Additionally, the use of the mutant strain as a vaccine provided good protection levels against both challenge strains.
Keywords: Attenuation; Chicken; Immune response; Reversion to virulence; Salmonella vaccine